THU0582 A systematic review of employment outcomes of adults with childhood-onset systemic autoimmune rheumatic diseases. (12th June 2018) - Gu, K.; Gottschalk, T.; Lim, L.S.H.
Abstract : Background: Childhood-onset systemic autoimmune rheumatic diseases (ChildCRD) include: systemic lupus erythematosus (SLE), Sjogren's syndrome, systemic sclerosis, inflammatory myositis, and chronic systemic vasculitides (Takayasu arteritis, polyarteritis nodosa, anti-neutrophil cytoplasmic antibodies (ANCA) associated systemic vasculitides). These conditions had mortality rates of up to 50%, but most patients now live into adulthood. Employment is an important milestone in adulthood: it has direct effects on one's socioeconomic status and access to health insurance, which could in turn affect disease outcomes. Objectives: To perform a systematic review of the employment outcomes of ChildCRD individuals. To identify gaps of knowledge and methodological issues in this field so as to inform future studies. Methods: ChildCRD patients have disease-onset <18 years old and adulthood outcomes reported at ≥18 years old. We developed a search strategy for employment outcomes of ChildCRD with an academic librarian; this was iteratively refined and finalised after peer-review by other librarians. We included English language articles published from Jan 1990 Oct 2017 in MEDLINE, EMBASE, and Scopus. Case reports, case series, editorials, letters, or short reports were excluded. We supplemented our search by hand-searching references in review articles. Information on outcomes, prognostic factors, and study designs was recorded. Studies were graded independently by 2 reviewers (after prior training for agreement) using the Quality in Prognosis Studies (QUIPS) risk-of-bias tool which examines quality in 6 study domains. Authors were contacted as necessary for further information or clarification. Results: Of 2109 studies, we identified 3 publications (G1) studying SLE patients. None studied other ChildCRD. Two papers were from a single study and studied both SLE and juvenile arthritis; we only used SLE patients' information. Three additional manuscripts (G2) studied childhood- and adult-onset patients but did not report outcomes separately. All G1 publications were from North America (2 Canada, 1 USA). 193 patients in 2 studies were examined; 1 study had longitudinal (non-inception) design. Only G1 studies have data for report. Patients' disease durations were a mean of 7.6–15 years and the mean ages at study were 23–29 years. Half of the patients were employed. Lower disease activity, better physical function, and higher education were associated with longitudinal employment in 1 study; greater independence and social support were associated with employment in another. One study showed psychosocial and work context factors to be associated with absenteeism, disease activity with job disruptions, and fatigue and work context factors with lost productivity. Of QUIPS-graded G1 publications, study populations and confounding were at moderate-high risk-of-bias. Study outcomes, prognostic factors, and statistical analyses were at low-moderate risks-of-bias. Attrition was low in the longitudinal study. Conclusions: Currently, there is minimal information on employment outcomes in ChildCRD adults except for few studies on SLE; information about other ChildCRD is needed. Study populations and confounding are at moderate-high risks-of-bias, limiting the generalizability. More information on employment outcomes, the specific aspects of employment, disease and non-disease related prognostic factors affecting employment are needed. Disclosure of Interest: None declared